Correlation Between Stress Level With the Incidence of Acne Vulgaris in Faculty of Medicine Students of the Swadaya Gunung Jati University - Frista Martha Rahayu; Muhammad Edial Sanif; Rizkia Alifa Fitriani; Permata Ayuning Tyas; Doni (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Acne vulgaris is a chronic inflammation disease of pilosebaceous glands with a polymorphic clinical picture of the skin consisting of comedones, pustules, nodules and scar tissue. One of the factors that cause acne vulgaris is stress. This study aims to determine whether there is a correlation between stress levels and acne vulgaris in FK UGJ students. This study is an analytic observational with a cross sectional approach using consecutive sampling technique. The sample consists of 121 respondents whose stress levels were assessed using a questionnaire and acne vulgaris condition was evaluated using both a questionnaire and clinical examination. Data analysis was performed using univariate analysis for frequency distribution and bivariate analysis using the chi-square test. The study found that 62% of respondents experienced acne vulgaris, with a predominance of females (65.1%) and aged 22 years (44%). The majority of respondents did not experience stress (43%), with a majority of females (37.2%) and aged 22 years (37.7%). Among those who did not experience stress, 57.7% had acne vulgaris. Based on the results of the analysis, the p-value was 0.360 (p-value>0.050). There is no significant correlation between stress levels and the incidence of acne vulgaris in students of the Faculty of Medicine, Universitas Swadaya Gunung Jati.